Nanoparticle-Based Combination Therapy for Cancer Treatment - Yhee, Ji Young; Son, Sejin; Lee, Hyukjin; Kim, Kwangmeyung (BENTHAM SCIENCE PUBL LTD, 2015)
In recent years, combination of different types of therapies using nanoparticles has emerged as an advanced strategy for cancer treatment. Most of all, combination of chemotherapeutic drug and siRNA in nanoformulation has shown a great potential, because siRNA-mediated specific gene silencing can compensate for the incomplete anti-cancer actions of chemotherapy. In this article, nanoparticle-based combination therapy for cancer treatment is introduced to be focused on the therapeutic chemical and siRNA combination. It is classified into 3 groups: 1) general chemotherapy combined with siRNA carrying nanoparticle, 2) co-delivery of chemical and siRNA therapeutics within a single nanoparticle, and 3) Use of multiple nanoparticles for chemical and siRNA therapeutics. The purpose of the combination and the mechanisms of anti-cancer action was described according to the categories. Examples of some recent developments of nanotechnology-based chemo-and siRNA-therapeutics combination therapy are summarized for better understanding of its practical application.
Keywords: GLYCOL CHITOSAN NANOPARTICLES; SIRNA-MEDIATED INHIBITION; DNA MISMATCH REPAIR; CO-DELIVERY; POLYMERIZED SIRNA; DRUG-DELIVERY; MULTIDRUG-RESISTANCE; DISACCHARIDE MOIETY; 1ST-LINE TREATMENT; TARGETED DELIVERY